Investigation of brucellosis in culled cows and professionals at El-Harrach’s slaughterhouse in Algeria - Akkou, M; Titouche, Y; Bentayeb, L; Ramdani-Bouguessa, N (Journal of the Hellenic Veterinary Medical Society, 2023)
¶In Algeria, despite control program (test/slaughter) applied since 1995, animal and human brucellosis incidence remains high over the last years. Our ¶Ou survey was carried out with, an aim of determining the insufficiencies of the applied prophylaxis plan, and assessing brucellosis hazard on professionals of slaughterhouse. ¶On top of the 31 visits performed at the slaughterhouse of El-Harrach, blood sera and data associated with: age, identification statute, race, type of slaughtering, pregnancy, and metritis presence were collected from 351 cull-cows¶. ¶From the cooperative professionals of the same establishment, 31 sera in conjunction with the socio-epidemiological data were sampled. ¶All sera were analyzed with Rose Bengal Plat Agglutination Test (RBPAT). ¶The obtained results showed 0% prevalence in the slaughterhouse workers, and a global rate of 4.56 % RBPAT positivity in the cull-cows, within 5.55% prevalence in the pregnant ones. A rate of 50% (28.6 to 83.3%) daily frequency appearance of a sero-positive cow at the slaughterhouse of El-Harrach was established. ¶In addition, 4.01% slaughtered cows in the framework of healthiness slaughtering, were positive. ¶While, no difference in prevalence related to race, neither to identification statute, nor for age, were recorded. ¶Indeed, one can expect that the uncontrolled movement of animals can evoke a substantial factor limiting the effectiveness of brucellosis control program.